2017
DOI: 10.1152/ajpheart.00249.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovariectomy on intracellular Ca2+ regulation in guinea pig cardiomyocytes

Abstract: 26This study addressed the hypothesis that long-term deficiency of ovarian hormones,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…However, an increase in Tau suggests impaired ‘active’ relaxation, likely related to alterations in calcium handling, which has been reported in other studies (Yang et al . ). The loss in stroke volume (and consequently in CO) in OVX does indicate that oestrogen depletion can contribute to impaired pump function.…”
Section: Discussionmentioning
confidence: 97%
“…However, an increase in Tau suggests impaired ‘active’ relaxation, likely related to alterations in calcium handling, which has been reported in other studies (Yang et al . ). The loss in stroke volume (and consequently in CO) in OVX does indicate that oestrogen depletion can contribute to impaired pump function.…”
Section: Discussionmentioning
confidence: 97%
“…Four experimental groups were generated: sham-operated control, transaortic constriction (AC), transaortic constriction with ovariectomy (ACOV), and transaortic constriction with ovariectomy supplemented with 17β-estradiol (ACOV+E). Animals initially underwent ovariectomy (OV) through a bilateral flank approach, in which both ovaries were surgically removed ( 8 ). A minimum of 7 days between the OV and AC procedures allowed appropriate recovery.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the long-term absence of ovarian hormones in the guinea pig leads to detrimental changes to intracellular Ca 2+ regulation in the heart, resulting in the formation of a proarrhythmic substrate ( 8 ). Studies on mice support the idea of Ca 2+ dysregulation following ovariectomy ( 9 , 10 ), and, in rats, it has been shown that estrogen can reduce incidence of arrhythmia following episodes of ischemia reperfusion ( 11 ).…”
mentioning
confidence: 99%
“…Interestingly, supplementation with either E 2 or progesterone prevents the OVX-related reductions in cardiac SERCA expression and activity and Thr17 PLB phosphorylation (77). However, Yang et al (92) reported that cardiomyocytes from OVX guinea pigs have 22% larger SR Ca 2+ stores and higher frequency of Ca 2+ sparks and waves than sham animals; addition of E 2 prevents these changes. Similarly, Howlett's group showed that the caffeine-induced SR Ca 2+ release signal, an indirect indicator of SR Ca 2+ content, is larger in cardiomyocytes from OVX than from sham C57BL/6 mice (74).…”
Section: Estrogen Gper and Serca2a And Its Regulatory Proteinsmentioning
confidence: 99%